2020
DOI: 10.1111/omi.12303
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Fusobacterium nucleatum growth in biofilm versus planktonic state

Abstract: Fusobacterium nucleatum is isolated from both supra‐ and sub‐gingival dental biofilms in humans and has been implicated in the aetiology of periodontitis. Also, this bacterium plays an important role in serious infections in other parts of the body. The aim of this investigation was to study the protein differential expression of F. nucleatum when growing on biofilm, compared to planktonic state, using proteomic analysis by the 2D‐DIGE™ system. In all, 68 proteins were differentially expressed during biofilm g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Nevertheless, our findings support the concept that oral health can be influenced by the oral microbiota, particularly when related to bacteria producing SCFAs. In support of this assumption, SCFAs were detected in gingival crevicular fluid subjects [ 15 , 16 ] partially originating from F. nucleatum [ 60 ]. According to our findings, butyrate and propionate are inhibitors of the inflammation-induced responses of macrophages, gingival fibroblasts, and also HSC2 oral epithelial cells, overall suggesting a beneficial effect of SCFAs for combat inflammatory tissue destruction.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, our findings support the concept that oral health can be influenced by the oral microbiota, particularly when related to bacteria producing SCFAs. In support of this assumption, SCFAs were detected in gingival crevicular fluid subjects [ 15 , 16 ] partially originating from F. nucleatum [ 60 ]. According to our findings, butyrate and propionate are inhibitors of the inflammation-induced responses of macrophages, gingival fibroblasts, and also HSC2 oral epithelial cells, overall suggesting a beneficial effect of SCFAs for combat inflammatory tissue destruction.…”
Section: Discussionmentioning
confidence: 94%
“…Dental plaque is the initiating and main pathogenic factor of periodontal disease. F. nucleatum is the dominant microorganism in periodontal tissues, and is associated with periodontitis etiology (Llama-Palacios et al, 2020). He et al (2012) showed that periodontally healthy individuals and patients with chronic periodontitis commonly experience F. nucleatum infection, F. nucleatum is more abundant in patients with chronic periodontitis.…”
Section: Association Between F Nucleatum and Periodontal Diseasementioning
confidence: 99%
“…H 2 S, which is the cause of oral malodor (Hampelska et al, 2020), can stimulate cell proliferation in CRC (Szabo et al, 2013). On the other hand, F. nucleatum is identified as a potential butyrate producer (Vital et al, 2014;Llama-Palacios et al, 2020;Dahlstrand Rudin et al, 2021). Unlike other bacteria, it does not rely on polysaccharides to produce butyrate but uses amino acids (Vital et al, 2014).…”
Section: The Biological Characteristics Of F Nucleatummentioning
confidence: 99%